The Oxford book of American short stories - Oates, Joyce Carol, 1938- (New York : Oxford University Press, 2013)
In The Oxford Book of American Short Stories, Joyce Carol Oates offers a sweeping survey of American short fiction, in a collection of nearly sixty tales that combines classic works with many "different, unexpected" gems, and that invites readers to explore a wealth of important pieces by women and minority writers.
Rip Van Winkle / Washington Irving -- Peter Rugg, the Missing Man / William Austin -- The Wives of the Dead / Nathaniel Hawthorne -- The Tell-Tale Heart / Edgar Allan Poe -- The Ghost in the Mill / Harriet Beecher Stowe -- The Paradise of Bachelors and the Tartarus of Maids / Herman Melville -- Cannibalism in the Cars / Samuel Clemens -- The Middle Years / Henry James -- A White Heron / Sarah Orne Jewett -- The Storm / Kate Chopin -- Old Woman Magoun / Mary e. Wilkins Freeman -- The Sheriff's Children / Charles Chesnutt -- The Yellow Wallpaper / Charlotte E Perkins Gilman -- A Journey / Edith Wharton -- The Little Regiment / Stephen Crane -- A Death in the Desert / Willa Cather -- The Strength of God / Sherwood Anderson -- In a Far Country / Jack London -- The Girl with a Pimply Face / William Carlos Williams -- The Rats in the Walls / H. P. Lovecraft -- Blood-Burning Moon / Jean Toomer -- An Alcoholic Case / F. Scott Fitzgerald -- That Evening Sun / William Faulkner -- Hills Like White Elephants / Ernest Hemingway -- Red-Headed Baby / Langston Hughes -- The Man Who Was Almost a Man / Richard Wright -- A Bottle of Milk for Mother / Nelson Algren -- Where Is the Voice Coming From? / Eudora Welty -- A Distant Episode / Paul Bowles -- The Country Husband / John Cheever -- Battle Royal / Ralph Ellison -- My Son the Murderer / Bernard Malamud -- The Lottery / Shirley Jackson -- There Will Come Soft Rains / Ray Bradbury -- Sonny's Blues / James Baldwin -- A Late Encounter with the Enemy / Flannery O'Connor -- The Shawl / Cynthia Ozark -- The School / Donald Barthelme -- The Persistence of Desire / John Updike -- Defender of the Faith / Philip Roth -- The Mud Below / Annie Proulx -- Are These Actual Miles? / Raymond Carver -- Heat / Joyce Carol Oates -- The Child Screams and Looks Back at You / Russell Banks -- Give It Up for Billy / Edmund White -- Under the Radar / Richard Ford -- Hunters in the Snow / Tobias Wolff -- The Things They Carried / Tim O'Brien -- The Reach / Stephen King -- Filthy with Things / T. C. Boyle -- Today Will Be a Quiet Day / Amy Hempel -- Fleur / Louise Erdrich -- The Drowned Life / Jeffrey Ford -- Children as Enemies / Ha Jin -- How to Become a Writer / Lorrie Moore -- Good People / David Foster Wallace -- Mercy / Pinckney Benedict -- Hell-Heaven / Jhumpa Lahiri -- Edison, New Jersey / Junot Diaz
Includes index.
Keywords: Short stories, American